Study on the possibility of application of a compact roll over protective structure for agricultural wheeled narrow track tractors - Danilo Monarca (Journal of Agricultural Engineering, 2013)
Since occupational accidents often occur in farm tractor drivers, it is extremely important to focus the attention on specific devices in order to avoid risks from tractor overturning. This phenomenon is actually considered as the leading cause of deaths or injuries related to agricultural work. The system adopted to reduce the above-mentioned risk consists of passive protection devices aimed at preventing the hazardous event which may affect workers’ health. More precisely, the tractor chassis (i.e. ROPS) and the proper seat belt define a “safety volume” around the worker. The aim of the present research is to carry out tests on narrow-track wheeled tractors with fixed roll over protective structures in those areas – such as hazel and olive groves and vineyards - where problems related to under–tree activities occur. This is to implement planting layout and/or cultivation techniques which can be considered suitable for tractors with roll over protective structures. According to that, their project parameters – i.e. safety volume, seat position and typology, test methods - can be successfully modified and improved. The results show that nowadays only a few agricultural vehicles are provided with specific fixed devices able to work under tree without damaging orchards.